Prevalence, Risk, and Challenges of Extemporaneous Preparation for Pediatric Patients in Developing Nations: A Review - Sri Hartati Yuliani; Dina Christin Ayuning Putri; Dita Maria Virginia; Michael Raharja Gani; Florentinus Dika Octa Riswanto (MDPI AG, 2023)
Extemporaneous preparations are still widely prescribed for pediatric patients with special treatments of certain doses and/or combinations of drugs. Several problems related to extemporaneous preparations have been linked to the incidence of adverse events or a lack of therapeutic effectiveness. Developing nations are facing the challenges of compounding practices. The prevalence of compounded medication in developing nations must be explored to determine the urgency of compounding practices. Furthermore, the risks and challenges are described and explained through investigation and collection of numerous scientific articles from reputable databases, including Web of Science, Scopus, and PubMed. Pediatric patients need compounded medication related to the appropriate dosage form and dosage adjustment. Notably, it is important to observe extemporaneous preparations in order to provide patient-oriented medication.